ANALISIS PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN TEMATIK MODEL JARING LABA-LABA DI SD NEGERI SUNGAI AMBAWANG - Kusrini, Kusrini; Kusrini, Mashudi; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problems of this research were focused on the planning, implementation and obstacles of applying scientific approach on thematic spider web learning model, aiming at making learners more active, critical thinking, the direct process experienced by the learners, the learning could be more meaningful, contekstual and fun. This research was conducted at  Public Primary School (SDN) 07 and  Public Primary School (SDN) 36 at Sungai Ambawang District. This is a descriptive qualitative research. The subjects of this research were the educators and the students of grade IV at SDN 07  and SDN 36 of Sungai Ambawang District. The techniques of data collection used were observation, interview, and documentation study. Data analysis was conducted through the steps: data reduction, data display, and conclusion. The technique for examining data validity was by triangulation. The results revealed that the educators have implemented the scientific approach on the thematic spider web learning model. The scientific approach implemented, includes: (1) observing, (2) questioning, (3) trying, (4) reasoning, and (5) communicating. The obstacles encountered in this lesson were lack of adequate facilities and infrastructure, the ability of their educators in mastering the learning strategy, and the low level  participation of some parents who were less concerned on their children education and also the different characteristics of  the learners. Keywords: scientific approach, thematic spider web learning model